The Book of Manāqib and Prophetic History - Heddy Shri Ahimsa-Putra (UIN Sunan Gunung Djati Bandung, 2014)
In order to understand and to read the book completely with high curiosity, historians and scholars of socio-cultural studies need to be not merely critical as usually required in every discipline, but also should be widely open-minded and fully aware that history has diverse meanings in accordance with perspective used to interpret it. Why? This is because this book is an unusual book of history in usual sense of the word. Although written using historical sources or written documents about empirical events occured in the past, this book discusses the meaning of history and its sources started with doubting or questioning—indirectly—various assumptions underlying historical inquiries that so far have been conducted. This book basically is a narration or story about the Book of Manaqib that describes the legend of famous Muslim scholar (‘ulama’, sing ‘alim) who was known among the Sufis as “Prince of Saints” (sultan al-awliya’) or “pole of saints” (wali al-qutb), Shaykh ‘Abd al-Qadir al-Jilani. Among Indonesian Muslims, he is popularly known as Syekh ‘Abdul Qadir Jaelani., Of course, this book does not simply discuss the life of this legendary scholar, but also discusses the position and the significance of the Book of Manaqib of Shaykh ‘Abd al-Qadir al-Jilani. The question remains, “what are the reasons leading Dr. Ajid to discuss such a book?” We can find the answer to this question throughout this book explicitly and implicitly.